Prospects for IT-Enabled Services Under a Indo-US FTA - Arpita Mukherjee; Paramita Deb Gupta (Indian Council for Research on International Economic Relations (ICRIER), 2006)
ITES/BPO services is an important and growing component of India's trade in services with the US. While the Indian government has implemented several measures to support the growth of this sector, Indian companies face various barriers in the US market such as anti-outsourcing regulations, restrictive visa/work permit regime and concerns relating to protection of sensitive data. Multilateral negotiations would have been the best route to address many of these barriers, but with the recent suspension of the Doha Round of talks, it has become important for countries to evaluate alternative routes such as bilateral Free Trade Agreements. In fact, after the suspension of the multilateral negotiations, both India and the US have refocused on bilateral agreements. In this context, this study discusses the current and potential trade between India and the US in ITES/BPO services, identifies barriers to trade and explores how an FTA can enhance bilateral trade in this sector. The study shows that the US-FTAs have achieved a higher level of liberalization than in the WTO. It suggests various negotiating strategies for India such as a negative list approach, signing mutual recognition agreements in key professional services, asking for a H1B1 type of visa, pushing for removal of domestic regulation-related barriers, among others which would enhance market access for Indian companies in the US. It also points out that Indo-US collaborations for data protection, skill development and raising awareness of the advantages of outsourcing in the US would be mutually beneficial. The study discusses regulatory and other reforms which will improve the productivity, efficiency and global competitiveness of this sector and enable the country to gain from the FTA.
Keywords: F13; F14; L86; 330; Indo-US FTA; GATS; Bilateral Agreements; business process outsourcing; IT-enabled services.